Microstructual Design of Lead Oxide-Epoxy Composites for Radiation Shielding Purposes - Noor Azman, N.; Siddiqui, Salim; Hart, Robin; Low, It-Meng (Jim) (John Wiley and Sons Inc, 2012)
Composite epoxy samples filled with PbO and Pb3O4 were fabricated to investigate the mass attenuation characteristics of the composites to X-rays in the diagnostic imaging energy range. The effect of density on the attenuation ability of the composites for radiation shielding purposes was studied using a calibrated X-ray machine. Characterization of the microstructure properties of the synthesized composites was performed using synchrotron radiation diffraction, optical microscopy, and scanning electron microscopy. The results indicate that the attenuation ability of the composites increased with an increase in density. The particle size of WO3 fillers has a negligible effect on the value of mass attenuation coefficient. Microstructural analyses have confirmed the existence of fairly uniform dispersion of fillers within the matrix of epoxy matrix with the average particle size of 1–5 μm for composites with filler loading of ≤ 30 wt % and 5–15 μm for composites with filler loading of ≥ 50 wt %.